Editorial - Allen, Franklin; Edmans, Alex (Review of Finance, 2017)
We are very grateful to everyone for their support of the Review of Finance (RF) in the past, through submitting, reviewing, or reading papers, being a personal or institutional subscriber, and informing others about the journal. We are pleased to have been added to the Financial Times 50 list, but this is only a start. Our goal is to be seen as an A journal, because we believe that our ever-expanding finance profession needs more than three A journals. We know that it will take a huge amount of effort to achieve this goal, but have made many changes to try to do so. We appreciate the opportunity to communicate these changes to our readers. We are pleased to announce a new Editorial Board at http://revfin.org/editorial-board. We thank the outgoing members for their distinguished service. We now have a common policy, across all editors, of applying the same standards as a top-three finance journal. The following text (or an Editor-specific variant thereof) is included in the invitation letter to referees: “Please apply a similar standard to what you would apply to the top-three finance journals. Because we receive a very large number of manuscripts, we are interested in publishing only papers that make a substantial contribution to knowledge that is of interest to a general finance audience. Competent useful extensions and qualifications of previous work, or analyses of narrower questions, are best left to specialized journals.”